Risk of Pesticide Exposure on Impaired Level of Intelligence (IQ) of Children - Suwondo, Ari; Widyawati, Melyana Nurul; Kurniawan, Bina; Dewi, Endah Kumala (KEMAS: Jurnal Kesehatan Masyarakat, 2021)
The shallot cropping pattern applied by farmers in the village of Pasir Demak is very likely to cause pollution. Pesticide contamination in pregnant women in the first trimester (3 months) can result in fetal death, low birth weight, and impaired intelligence (IQ). Preliminary research conducted in 2016 found that elementary schooler who came from Pasir Village, Demak had low learning achievement. It was an observational study with a cross-sectional approach; the respondents were Elementary Schooler grades 4, 5, and 6 (107 people) and the mothers of the students (107 people). Thus, the total respondents were 214 people. The IQ assessment instrument used the SPM and CPM instruments. The level of pesticide poisoning from the mother was to measure blood Cholin Esterase levels using a tintometer, the data were then statistically analyzed using Chi Square and Odd Ratio for risk factors. There were significant differences on the level of intelligence of children including the planting system p=0.002; room area p=0.047; ventilation area p=0.041; type of pesticide p=0.001; spraying before harvest p=0.007; spraying after harvest p=0.008; storage place for crop yields p=0.039, while the variables that did not show significant difference were the playing environment p=0.848; gestational age p=0.190; contact to pesticides p=0.105 and age p=0.418. Pesticide contamination in pregnant women in the 1st trimester which the time to process formation and development of the brain in the Temporal lobe and Frontal lobe will experience impaired learning and memory (IQ). Keywords : Elementary schooler; Pesticide exposure; Level of intelligence.